(untitled) (Studying the History of Higher Education Journal, 2024)
The onset of World War II drove the American government to seek support from universities across the nation to educate officers in the service in the language and customs of Japan. The University of Colorado Boulder played a significant role in hosting the U.S. Navy Japanese Language School from 1942 to 1946, and in training officers in the Japanese language. Many of the school’s graduates contributed significantly to the war efforts. This article explores the origins and evolution of the Japanese Language School at CU Boulder, providing a historical overview of the factors behind the school’s formation and the actions of its organizer Commander Albert E. Hindmarsh. Rooted in primary and secondary sources, including those from the University of Colorado Boulder libraries archives, the article traces the school’s establishment in the context of the strained relations between the U.S. and Japan, and discusses the invaluable role of its graduates to the war effort. In addition to teaching the Japanese language, the school and its teachers played a critical role in fostering positive relationships with the locals and addressing stereotypes. Graduates, both men and women, forged careers in diverse fields, becoming ambassadors for Japanese culture and language. The legacy of the Boulder school lives on in the various Japanese language programs existing across the country and in the personal transformations of those involved.